Suicide Postvention in the Department of Defense Evidence, Policies and Procedures, and Perspectives of Loss Survivors - Ramchand, Rajeev (RAND Corporation, 2015)
A review of the scientific evidence on suicide postvention (organizational responses to prevent additional suicides and help loss survivors cope), guidance for other types of organizations, and the perspectives of the family and friends of service members who have died by suicide provide insights that may help the U.S. Department of Defense formulate its own policies and programs in a practical and efficient way.